Implementation of Containerization on Village Information Systems (OpenSID) Using Docker for Server Resource Efficiency - I Wayan Yudik Pradnyana; I Wayan Ady Juliantara (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The digitalization of village governance in Indonesia faces significant challenges in the form of inconsistencies in the server environment (environment drift) that hinder the stability and scalability of the Village Information System (OpenSID). This research aims to implement the Container-Based Deployment method as an operational approach based on the DevOps paradigm to standardize village digital infrastructure. The method used is Infrastructure as Code (IaC) by integrating OpenSID applications and MariaDB databases into isolated Docker containers, with service access through specific port mapping for both primary application access and database management. The results showed that the use of containerization successfully overcame the complexity of manual configuration, with a 100% success rate of meeting system dependencies. This architecture allows for identical system replication, deployment time efficiency, and ease of service access. This research produces a reliable, portable, and efficient system architecture model for village governments in supporting the transformation of digital public services that are more stable and accessible.